Front Cover: Targeting the Liver‐Brain Axis with Hop‐Derived Flavonoids Improves Lipid Metabolism and Cognitive Performance in Mice. Issue 15 (4th August 2020) - Paraiso, Ines L.; Revel, Johana S.; Choi, Jaewoo; Miranda, Cristobal L.; Lak, Parnian; Kioussi, Chrissa; Bobe, Gerd; Gombart, Adrian F.; Raber, Jacob; Maier, Claudia S.; Stevens, Jan F.
Abstract : Mol. Nutr. Food Res . 2020, 64, 2000341 DOI: 10.1002/mnfr.202000341 Xanthohumol (XN), a flavonoid from hops (Humulus lupulus), and its hydrogenated derivatives, α, β‐dihydroxanthohumol (DXN) and tetrahydroxanthohumol (TXN) decrease hepatic cholesterol by enhancing de novo synthesis of bile acids and decrease ceramide content in liver and hippocampus. The subsequent amelioration of obesity‐induced metabolic and neurocognitive impairments suggests that XN, DXN, and TXN may mitigate metabolic syndrome by targeting the liver‐brain axis. This is reported by Ines L. Paraiso, Johana S. Revel, Jaewoo Choi, Cristobal L. Miranda, Parnian Lak, Chrissa Kioussi, Gerd Bobe, Adrian F. Gombart, Jacob Raber, Claudia S. Maier, Jan F. Stevens in article 2000341 .